2011
DOI: 10.1261/rna.2789611
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling regulation and new components of human P-bodies through a protein interaction framework and experimental validation

Abstract: The cellular factors involved in mRNA degradation and translation repression can aggregate into cytoplasmic domains known as GW bodies or mRNA processing bodies (P-bodies). However, current understanding of P-bodies, especially the regulatory aspect, remains relatively fragmentary. To provide a framework for studying the mechanisms and regulation of P-body formation, maintenance, and disassembly, we compiled a list of P-body proteins found in various species and further grouped both reported and predicted huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 130 publications
2
37
0
Order By: Relevance
“…One candidate is RO52/TRIM21, which colocalizes with the deubiquitylating enzyme USP4 to P-bodies. Knockdown of both proteins reduces P-body numbers by unknown mechanisms (Zheng et al, 2011). Our results add another facet to the multifunctional TRAF6 protein that is known to integrate into a plethora of signaling complexes (Walsh et al, 2015).…”
Section: Discussionmentioning
confidence: 66%
“…One candidate is RO52/TRIM21, which colocalizes with the deubiquitylating enzyme USP4 to P-bodies. Knockdown of both proteins reduces P-body numbers by unknown mechanisms (Zheng et al, 2011). Our results add another facet to the multifunctional TRAF6 protein that is known to integrate into a plethora of signaling complexes (Walsh et al, 2015).…”
Section: Discussionmentioning
confidence: 66%
“…In contrast, a study reported that TOB1 is constitutively expressed in liver and its downregulation is required for normal liver regeneration (17). Furthermore, TOB2 and not TOB1 was found to colocalize with mRNA-processing bodies (13) that contain nontranslating mRNAs, as well as proteins involved in translational inhibition and mRNA degradation (3,12,15,30,44). It will be interesting to identify the different features of the TOB proteins that are responsible for these specific functions and to decipher the mechanisms controlling and/or coordinating the multiple actions of these two functionally important but redundant proteins.…”
Section: Discussionmentioning
confidence: 98%
“…Several cellular factors involved in posttranscriptional regulation comprise P bodies (14); however, how such a factor(s) promotes controlled P-body assembly in response to TGF-␤ signaling is not known. Based on the ability of TTP to promote AREmediated decay and localize to P bodies (41, 42), we sought to determine if a causal link exists between TTP and TGF-␤-mediated P-body formation.…”
Section: Tgf-␤ Promotes P-body Formationmentioning
confidence: 99%
“…In many cases, ARE-mRNAs targeted for rapid decay require the components necessary for 5=-to-3= degradation and are localized to processing (P) bodies (11)(12)(13). These small cytoplasmic foci contain the components of the 5=-to-3= decay machinery along with other factors involved in microRNA (miRNA)-and small interfering RNA (siRNA)-mediated silencing, nonsense-mediated decay, and translational silencing (14). P-body assembly is a dynamic process that is tightly linked with the availability of free cytoplasmic mRNAs that drives the aggregation of mRNA-protein complexes in the cytoplasm into microscopically visible P bodies (15,16).…”
mentioning
confidence: 99%